HUBUNGAN ANTARA PERSEPSI TERHADAP HARAPAN ORANGTUA DENGAN MOTIVASI BERPRESTASI PADA SISWA SMP NEGERI 31 SEMARANG - Wahyu Kusumaningtyas; Endah Kumala Dewi; Jati Ariati (Jurnal EMPATI, 2013)
The successful of student in education showed with academic achievement. Achievement motivation is needed to be able to inspire students in achieving performance targets or desired standards. Expectation of every parent develop their children. The parents hope will be perceived by the students. Students will assess parental expectations, the results of which are owned interpretation will affect students achievement motivation. The purpose of this study was to determine the relationship between perception of parental expectations and achievement motivation in students of SMP Negeri 31 Semarang and to determine the effective contribution of the variable perceptions of parental expectations on achievement motivation.            The population in this study were 495 students seventh grade and eighth grade SMP Negeri 31 Semarang. Sampling technique using cluster random sampling technique. Methods of data collection using two scales psychology, namely Achievement Motivation Scale with α = 0.865 and Perceptions of Parents Expectations scale with α = 0.886. The results were analyzed using simple regression analysis.            The results of study showed coefficients rxy = 0.448 with a significance level of correlation p=0.000 (p <0.05), which means that hypothesis is accepted. Effective contribution to the perception of parents expectations are for 20% of the students achievement motivation and 80% are other factors that also contribute to achievement motivation affects not revealed in this study.